Global software engineering : virtualization and coordination - Wiredu, Gamel O. (Boca Raton, FL : CRC Press, 2020)
Technology and organizations co-evolve, as is illustrated by the growth of information and communication technology (ICT) and global software engineering (GSE). Technology has enabled the development of innovations in GSE. The literature on GSE has emphasized the role of the organization at the expense of technology. This book explores the role of technology in the evolution of globally distributed software engineering. To date, the role of the organization has been examined in coordinating GSE activities because of the prevalence of the logic of rationality (i.e., the efficiency ethos, mechanical methods, and mathematical analysis) and indeterminacy (i.e., the effectiveness ethos, natural methods, and functional analysis). This logic neglects the coordination role of ICT. However, GSE itself is an organizational mode that is technology-begotten, technology-dominated, and technology-driven, as is its coordination. GSE is a direct reflection of ICT innovation, change, and use, yet research into the role technology of GSE has been neglected. Global Software Engineering: Virtualization and Coordination considers existing fragmented explanations and perspectives in GSE research, poses new questions about GSE, and proposes a framework based on the logic of virtuality (i.e., creativity ethos, electrical methods, and technological analysis) rather than of rationality and indeterminacy. Virtuality is the primary perspective in this book's comprehensive study of GSE. The book concludes with an integrated explanation of GSE coordination made possible through ICT connectivity and capitalization.
Chapter 1. IntroductionChapter 2. Coordination TheoryChapter 3. Logic of VirtualityChapter 4. Materiality of TechnologyChapter 5. Management of InformationChapter 6. Exploitation of GeographyChapter 7. Paradox of OrganizationChapter 8. Virtuality of CoordinationChapter 9. Illustration of CoordinationChapter 10. ReflectionsAppendix
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering; BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology; COMPUTERS / Programming / Software Development